Antagonism of Cerebral High Mobility Group Box 1 Ameliorates Dendritic Cell Dysfunction in Sepsis - Ren, Chao; Yao, Ren-qi; Wang, Li-xue; Li, Jun-cong; Chen, Kun-wei; Wu, Yao; Dong, Ning; Feng, Yong-wen; Yao, Yong-ming (Frontiers in Pharmacology, 2021)
Sepsis has emerged as a global health issue, and accounts for millions of deaths in intensive care units. Dysregulation of the immune response reportedly contributes to the pathogenesis and progression of this lethal condition, which involves both the dysfunction of immune cells and incompetent immunomodulatory mechanisms. High mobility group box 1 (HMGB1) is known as a later inflammatory mediator and is critically involved in the severity and prognosis of sepsis by inducing intractable inflammation and dysfunction of various immune cells. In the present study, we found that intracerebroventricular (ICV) injection of Box A, a specific antagonist of HMGB1, restored the dysregulated response of splenic dendritic cells (DCs) in septic mice by enhancing the expression of surface molecules, including CD80, CD86 and MHC-II, as well as improving DC priming of T lymphocytes. Cerebral HMGB1 was also confirmed to have potent inhibitory effects on DC functions when administrated by ICV injection in normal mice. The brain cholinergic system was found to mediate the immunomodulatory effects of central HMGB1, as it exhibited enhanced activity with persistent HMGB1 exposure. Furthermore, the inhibitory effects of cerebral HMGB1 on the response of peripheral DCs were also blocked by α7nAchR gene knockout. These findings provide novel insight into the relationship between cerebral HMGB1 and splenic DC dysfunction during sepsis, which is, at least in part, dependent on cholinergic system activity.